Incidencia de las actividades físicas-recreativas para mejorar la movilidad articular en los adultos mayores, del Sector Piedra Grande, del Cantón Ventanas, Provincia de Los Ríos - Lucio Ayala, Evelyn Jesús (2022)
This research is aimed at analyzing the incidence of physical and recreational activities to improve joint mobility in older adults in the Piedra Grande Sector, in the Ventanas Canton. Methodology: a quantitative research was developed, of non-experimental design – cross-sectional and of a descriptive-propositional type. To do this, the researchers selected an intentional sample of approximately seven older adults from the Piedra Grande Sector, in the Ventanas Canton. Two instruments were implemented for data collection: 1) questionnaire of structured questions (survey) to determine the degree of knowledge that older adults have about the physical-recreational activities they perform and their mood; 2) Senior Fitness Test to diagnose the level of joint mobility in the elderly of the Piedra Grande Sector, of the Ventanas Canton. Results: It was found that older adults mostly lack joint mobility. Regarding the evaluation of the upper and lower train, 85.72% had a "very low" joint mobility; while 14.28% have "normal" joint mobility. According to the validation of hypotheses through Pearson's Chi-Square statistical test, acceptance of the null hypothesis was obtained (there are no significant differences in the development of joint mobility of older adults in the Piedra Grande Sector, in the Ventanas Canton). Proposal: a plan of physical and recreational activities was developed aimed at improving the joint mobility of the elderly of the Piedra Grande Sector, in the Ventanas Canton, which is designed to be applied for six months.